What's your favorite food or drink?
Answer:
Step-by-step explanation:
Formula for the volume of a sphere is V = (4/3) (π) r³
3V 4²
and so the cube of the radius, "r," is r³ = ------------- * -----
4 4²
Taking the cube root of both sides, we get
∛[3V / 4²] 3V
and so the radius, "r," is r = ------------------ = ∛ ( --------- ) = (1/4)*∛(3*v)
∛[4³] 4³
Then
r = (1/4)*∛(3*V), after substituting 500/(3π) for V, becomes:
r = (1/4)*∛[ 3*500/3π ] = (1/4)*∛[ 500/π ]
Answer: n = 3; n represents a remainder in a division problem.
Explanation:
1) Finding n:
i) Given: 643 = 4 × 160 + n
ii) Do the operations: 643 = 640 + n
iii) Subraction property of the equality: 643 - 640 = n
iv) Do the operations: 3 = n
Answer: n 3
2) Meaning of n
When you divide 643 by 4 the quotient is 160 and the remainder is 3, because 160 × 4 = 640, and 643 - 640 = 3.
This is, 3 is what is left when you split 643 into 4 getting 160 whole parts (plus the remainder, 3).
Answer:
I think this is a pretty good question of law of indices
Step-by-step explanation:
Given that
![(9^p)(27^q)=3^n\\](https://tex.z-dn.net/?f=%289%5Ep%29%2827%5Eq%29%3D3%5En%5C%5C)
a) express n in terms of p and q ,
b) hence if p = 1 and q = 2 find the value of n
Solution to part a)
![(9^p)(27^q)=3^n\\\\](https://tex.z-dn.net/?f=%289%5Ep%29%2827%5Eq%29%3D3%5En%5C%5C%5C%5C)
Simplify the equation and how do we do that? As we can see that 9 can also be written as 3^2 and 27 can be written as 3^3 we can rewrite the following equation like this,
![(3^2)^p(3^3)^q=3^n\\](https://tex.z-dn.net/?f=%283%5E2%29%5Ep%283%5E3%29%5Eq%3D3%5En%5C%5C)
now we multiply p with 2 and
multiply q with 3 respectively,
![(3^{2p})(3^{3q})=3^n\\](https://tex.z-dn.net/?f=%283%5E%7B2p%7D%29%283%5E%7B3q%7D%29%3D3%5En%5C%5C)
now since the bases are same and are multiplying the exponents will add themselves like this, in this equation the number 3 is the base
![3^{2p+3q}=3^n\\](https://tex.z-dn.net/?f=3%5E%7B2p%2B3q%7D%3D3%5En%5C%5C)
now since the bases on the left hand side and on the right hand side are equal the exponents will also be equal so now,
![2p+3q=n\\](https://tex.z-dn.net/?f=2p%2B3q%3Dn%5C%5C)
hence n is expressed in terms of p and q
Solution to part b)
if p = 1 and q = 2 we plug in these values in the above equation we found for n
n = 2p + 3q
n = 2(1) + 3(2)
n = 2 + 6
n = 7